2014
DOI: 10.1002/ijch.201400001
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the Protein Universe using Classifications, Maps, and Networks

Abstract: A meaningful and coherent global picture of the protein universe is needed to better understand protein evolution and the underlying biophysics. We survey the studies that tackled this fundamental challenge, providing a glimpse of the protein space. A global picture represents all known local relationships among proteins, and needs to do so in a comprehensive and accurate manner. Three types of global representations can be used: classifications, maps, and networks. In these, the local relationships are derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Different techniques have previously been explored in order to generate global representations of protein structure space (see, for example, [ 11 ]). Commonly, these approaches utilise structural similarities between protein domains, which produce complex, multi-dimensional data structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different techniques have previously been explored in order to generate global representations of protein structure space (see, for example, [ 11 ]). Commonly, these approaches utilise structural similarities between protein domains, which produce complex, multi-dimensional data structures.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative is to use networks to capture relationships resulting from significant alignments [ 13 , 22 30 ]. Unlike multidimensional scaling approaches, network constructions do not assume that structural similarity between protein domains is transitive [ 11 ]. On the other hand, they do require a score threshold to be set: above which an alignment is considered significant.…”
Section: Introductionmentioning
confidence: 99%
“…There are different approaches to forming a global view of the protein universe (18). The most significant efforts are the ones embodied in the hierarchical classifications CATH and SCOP.…”
mentioning
confidence: 99%
“…On the other hand, the highly connected hubs form an integral part of the network, leaving them vulnerable to targeted attacks (Cohen et al, 2001). Translating this graph theory notion to cancer networks, cancer-associated proteins and their interactions are mapped to nodes and their edges (Ben-Tal et al, 2014). Previous studies have suggested scale-free network architectures in glioblastoma (Ladha et al, 2010), gastric cancer (Aggarwal et al, 2006), and colon cancer (Ruan et al, 2006) though these results are based partially or primarily on correlations in gene expression, a surrogate for network edges.…”
Section: Introductionmentioning
confidence: 99%